2019
DOI: 10.1186/s13075-019-1884-0
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain precedes the development of new knee pain in the elderly population; a novel predictive score from a longitudinal cohort study

Abstract: Background To investigate the association between knee pain and risk factors including low back pain and to develop a score to predict new knee pain in an older population, using population-based longitudinal cohort data. Methods We collected a questionnaire on self-reported knee pain and demographic data in a systematic manner from community residents aged ≥ 50 years twice, at baseline, and after 5 years. Multivariate logistic regression analyses were performed to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Some authors reported the association between LBP and hand or foot [31], knee [12,28], shoulder [31], and neck pain [11] in cross-sectional studies. There have also been a small number of longitudinal studies regarding the association between LBP and each musculoskeletal pain, and preexisting LBP was reported to be associated with onset of knee [27] and neck pain [10]. To our knowledge, the present study was the first to report that preexisting knee and neck pain were individually associated with onset of LBP, even if the effect of the other musculoskeletal pain was considered.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Some authors reported the association between LBP and hand or foot [31], knee [12,28], shoulder [31], and neck pain [11] in cross-sectional studies. There have also been a small number of longitudinal studies regarding the association between LBP and each musculoskeletal pain, and preexisting LBP was reported to be associated with onset of knee [27] and neck pain [10]. To our knowledge, the present study was the first to report that preexisting knee and neck pain were individually associated with onset of LBP, even if the effect of the other musculoskeletal pain was considered.…”
Section: Discussionmentioning
confidence: 63%
“…There has been speculation in the literature about the association between concurrent pain at different sites. Pain at one site can negatively affect motion or posture and place additional burden on the other parts of the body [27]. The factors associated with one pain can also be related to the other pain [28].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported the association between LBP and hand or foot [31], knee [12,28], shoulder [31], and neck pain [11] in cross-sectional studies. There have also been a small number of longitudinal studies regarding the association between LBP and each musculoskeletal pain, and preexisting LBP was reported to be associated with onset of knee [27] and neck pain [10]. To our knowledge, the present study was the first to report that preexisting knee and neck pain were individually associated with onset of LBP, even if the effect of the other musculoskeletal pain was considered.…”
Section: Discussionmentioning
confidence: 57%
“…Clinical reports have documented patients with co-occurring LSS and hip OA [ 27 , 33 ], but the relationship with co-occurring knee OA [ 34 ], is relatively unknown. However, there is evidence suggesting knee OA and low back pain commonly co-exist [ 24 ] and low back pain has been identified as a risk factor for the development of knee pain in older adults [ 35 ]. A recent study also found the presence of radiographic knee OA was associated with all phenotypes of spinal OA (odds ratios ranging from 1.8 to 4.3) [ 36 ], which may represent the spinal changes found in LSS.…”
Section: Introductionmentioning
confidence: 99%